DISCLOSURE OF PUBLIC INFORMATION TO PROMOTE GOVERNMENT TRANSPARENCY AND ACCOUNTABILITY IN THE INTERESTS OF THE COMMUNITY - Erliza, Tista; Zahrina, Putri; Fahira, Nadia (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Law no. 14 of 2008 which regulates Openness of Public Information has fulfilled one of the human rights and given new hope to every Indonesian citizen in terms of obtaining information. This law guarantees the right for every citizen to obtain information. Through this law, the government is required to provide information regularly to its citizens so that they can know what the government has done. It is hoped that through this openness of information, the community will have an active role in both the monitoring aspect, the implementation aspect and the aspect of involvement in the decision-making process. Through openness of information, transparency and accountability will be realized for the community, so that a harmonious relationship can be established between the government and citizens in efforts to run the government.